Serum Apelin Levels and Correlation with illness Severity in Nonobese Patients with Bronchial Asthma - Rohan Pattanaik; Pratima Kumari Sahu; Monalisa Mohapatro; Jeetendra Kumar Patra; Nirjharini Dhal (International Journal of Advanced Medical and Health Research)
Background: Asthma is one of the most common chronic diseases globally. It is characterized by airflow obstruction that varies markedly, regardless of treatment. It is a type of airway inflammation due to bronchial hyperresponsiveness to a wide range of allergens, leading to excessive, usually reversible, airway narrowing. Asthma occurs more frequently in obese people, and it may be linked to pro-inflammatory adipokines. Apelin, a bioactive peptide belonging to the adipokines group, is identified as an endogenous ligand of an orphan G-protein coupled receptor named Apelin receptor (AR or APJ). Apelin is demonstrated in mature adipocytes and is highly expressed in pulmonary tissue, including bronchial and alveolar epithelial cells and small pulmonary blood vessels. Aim: The aim of this study was to evaluate the level of serum apelin in adult nonobese patients diagnosed with bronchial asthma cases and compare with healthy volunteers. We also aimed to correlate serum apelin levels with the severity of bronchial asthma. Materials and Methods: Twenty-two nonobese clinically diagnosed cases of bronchial asthma were included as cases and 66 age, sex, and socio-economic status-matched healthy volunteers as controls. Body mass index of cases and control subjects was calculated by weight (kg) per height (m2). Pulmonary function tests of the cases were done using spirometry. Serum apelin levels were estimated using Abbkine human ELISA-based kit. Statistical analysis was done using Pearson’s correlation test and analysis of variance. Results: We recruited 22 nonobese bronchial asthma cases (mean age = 38.2 ± 10.5 years) and 66 matched controls (mean age = 39.5 ± 12.0 years. Majority of the sample were females (n = 19 cases [86.3%], 54 controls [81.8%]). The mean serum apelin levels in cases and controls were 1355.3 ± 781.0 ng/L and 725.9 ± 375.6 ng/L, respectively; this difference was statistically significant (t = 5.053, df = 86, p = 0.001). The mean serum apelin levels in mild and moderate cases of bronchial asthma were 1121.5 ± 535.9 ng/L and 2150.2 ± 1019.1 ng/L, respectively. This difference was also statistically significant (t = 3.06, df = 20, p = 0.01). Conclusion: Serum apelin levels differ significantly between adult patients with bronchial asthma and population controls. Further, serum apelin levels differed with illness severity. These findings have important implications for disease management.